Penerapan Terapi Modifikasi Perilaku dengan Teknik Shaping untuk Membentuk Kemandirian Anak - Nurul Malika (International Consortium of Education and Culture Research Studies, 2020)
This study aims to intervene in children who are under the age category of toddlers with an attitude of independence in one kindergarten in Sampang, Madura. The method used in research is an experimental case study approach. Researchers provide interventions in the form of behavioral therapy, using Shaping techniques to bring up new behaviors that have not been displayed by children by providing reinforcement in every targeted behavior. This therapy can train children repeatedly with stages of modeling, imitating and taking the initiative to conduct targeted behavior interspersed with the reinforcement given. Children with this therapy will learn new behavioral patterns and learn slowly to apply and later become habitual behavior patterns. The independence formed by children here by maximizing limbs and moving the body to be able to themselves with simple class activities such as cursing shoes, taking and placing books, and taking the water they carry, which is usually through the teacher to fetch. The results of the application of shaping techniques for children are more learning and understanding that he must be independent at school and should not be accustomed to his behavior at home, even though the factors causing the independence are due to behavior patterns or treatment from his family (pampering).